Case Report: DPM1-CDG: Novel Variant with Severe Phenotype and Literature Review - Lausmann, Hanna; Zacharias, Martin; Neuhann, Teresa M.; Locher, Melanie K.; Schettler, Karl F. (Frontiers in Genetics, 2022)
Background: Congenital disorders of glycosylation (CDG) type I include variants in the DPM1 gene leading to DPM1-CDG. The nine previously reported patients showed developmental delay, seizures, EEG abnormalities and dysmorphic features with varying disease onset and severity. Methods: Clinical features of a new patient are described. Whole exome sequencing using NGS was performed, followed by molecular simulation of the structural changes in the protein. Results: Our patient with DPM1-CDG presented with more severe symptoms and an earlier onset, specifically non-febrile seizures from the age of three weeks, global developmental delay, and severely retarded motor skills. She died at the age of eleven weeks after fulminant sepsis. We identified compound heterozygous variants in the DPM1 gene, one previously reported point mutation c.1A>C p.?, as well as the novel variant c.239_241del p.(Lys80del), resulting in the first in-frame deletion located in exon 2. Loss of Lys80 may lead to an impaired α-helical configuration next to the GDP/GTP binding site. Conclusions: The presented case extends the spectrum of DPM1-CDG to a very young and severely affected child. The deletion of Lys80 in DPM1 results in an impaired helical configuration. This has implications for further understanding the association of structure and function of DPM1.